(untitled) (مجلة إحالات, 2025)
الملخص: لقد خلّف غياب المعرفة الدقيقة بآليات الترجمة ونقل النصوص الأدبية تشويها لغويا تاهت فيه المعاني وسط معترك لغوّي مفتوح يشوبه الاختلاف، من هذا المنطلق جاءت دراستنا لتسلط الضوء على عدّة نقاط رأينا بأن لها من الأهمية ما يجعلها مجالا بحثيا يحتاج تفكيكا وتحليلا حتى يتسنى لنا إعطاء تصوّر منهجي نستطيع من خلاله تلمس النقائص المنهجية التي تفضي إلى ترجمة أكثر كمالا تؤدي المعنى كاملا داخل قالب لغوي يستوعب النصّ الأصل، منطلقين في ذلك من عدّة إشكاليات أهمها: - ما هي الأليات، وأهم الإشكاليات والعوائق التي تطرح نفسها كنقاط مؤثرة في عملية الترجمة؟ - كيف يمكن للمصطلح المترجم أن يؤدي الوظيفة بصفة تكاملية يتجاوز من خلالها تشوية المعنى؟ - كيف يمكن للباحث أن ينقل المعرفة النقدية من الإطار النظري إلى الإطار الإجرائي دون إخلال بمعايير الفاعلية؟ - ما هي المقاربة التي يجب انتهاجها في تأطير النص النقدي ورسم أبعاده الدلالية والإجرائية؟ Abstract: The absence of precise knowledge of the mechanisms of translation and the transmission of literary texts has left a linguistic distortion in which the meanings have been lost in the midst of an open linguistic encounter that is subject to difference. In this sense, our study came to shed light on several points that we saw as important. Through which we can see the methodological deficiencies that lead to a more complete translation that leads to the full meaning within a linguistic template that accommodates the original text, starting with several problems, the most important of which are: - What are the mechanisms and the most important problems and obstacles that present themselves as influential points in the translation process? - How can the translated term perform the function in an integrative way beyond which the meaning is distorted? - How can the researcher transfer critical knowledge from the theoretical framework to the procedural framework without compromising the standards of effectiveness? -What approach should be taken in framing the monetary text and drawing its semantic and procedural dimensions?